2022
DOI: 10.1038/s41557-021-00839-3
|View full text |Cite
|
Sign up to set email alerts
|

Release of linker histone from the nucleosome driven by polyelectrolyte competition with a disordered protein

Abstract: Proteins with highly charged disordered regions are abundant in the nucleus, where many of them interact with nucleic acids and control key processes such as transcription. The functional advantages conferred by protein disorder, however, have largely remained unclear. Here we show that disorder can facilitate a remarkable regulatory mechanism involving molecular competition. Single-molecule experiments demonstrate that the human linker histone H1 binds to the nucleosome with ultra-high affinity. However, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 97 publications
1
47
0
Order By: Relevance
“…34,35 Further, molecular dynamics simulations have suggested that the GD and the bound linker DNA strands are dynamic in the chromatosome. 18,19,27,[34][35][36] This is supported by experimental observations from fluorescent recovery after photobleaching (FRAP) experiments showing shorter residence times of H1 compared to core histones, 15 and the lower local resolutions of H1-GDs compared to core histones in density maps. 18 Collectively, the recent progress in understanding the structure and dynamics of H1 in chromatosomes suggests that the position of charged side chains on the GD influence chromatin structure and gene repression.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…34,35 Further, molecular dynamics simulations have suggested that the GD and the bound linker DNA strands are dynamic in the chromatosome. 18,19,27,[34][35][36] This is supported by experimental observations from fluorescent recovery after photobleaching (FRAP) experiments showing shorter residence times of H1 compared to core histones, 15 and the lower local resolutions of H1-GDs compared to core histones in density maps. 18 Collectively, the recent progress in understanding the structure and dynamics of H1 in chromatosomes suggests that the position of charged side chains on the GD influence chromatin structure and gene repression.…”
Section: Introductionmentioning
confidence: 64%
“…The role of the disordered C-tail has been more challenging to pinpoint; however, the C-tail has been known to increase the affinity for, and residence time on, DNA, 7,[15][16][17] and it affects the assembly of higher-order chromatin structures and controls the openness of the linker DNA. 3,18,19 According to a recent model, the C-tail remains fully disordered in H1 bound to the nucleosome and makes extensive interactions with the linker DNA. 19 The biological role and native occurrence of the off-dyad binding mode remain debated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulations reported here were performed in the absence of excess salt or solution ions (if the systems were electroneutral, see SI Appendix ). Solutions ions are likely to play an important role in affecting conformational transitions, conformational equilibria, binding equilibria, and phase equilibria of polyampholytic and polyelectrolytic IDRs (24, 39, 51, 83, 89-91). Besides the screening effect, predicted by Higgs and Joanny (64), there is the expectation that ions that preferentially accumulate around blocks of the same type of charge are released when the ion-chain interactions are replaced by intra-chain interactions (91, 92).…”
Section: Discussionmentioning
confidence: 99%
“…Solutions ions are likely to play an important role in affecting conformational transitions, conformational equilibria, binding equilibria, and phase equilibria of polyampholytic and polyelectrolytic IDRs (24, 39, 51, 83, 89-91). Besides the screening effect, predicted by Higgs and Joanny (64), there is the expectation that ions that preferentially accumulate around blocks of the same type of charge are released when the ion-chain interactions are replaced by intra-chain interactions (91, 92). The effects of solution ions are also likely to be directly relevant to the phase behaviors of polyampholytic IDRs (93, 94).…”
Section: Discussionmentioning
confidence: 99%